Simulating Dynamics of Circulation in the Awake State and Different Stages of Sleep Using Non-autonomous Mathematical Model With Time Delay - Karavaev, Anatoly S.; Ishbulatov, Yurii M.; Prokhorov, Mikhail D.; Ponomarenko, Vladimir I.; Kiselev, Anton R.; Runnova, Anastasiia E.; Hramkov, Alexey N.; Semyachkina-Glushkovskaya, Oxana V.; Kurths, Jürgen; Penzel, Thomas (Frontiers in Physiology, 2021)
We propose a mathematical model of the human cardiovascular system. The model allows one to simulate the main heart rate, its variability under the influence of the autonomic nervous system, breathing process, and oscillations of blood pressure. For the first time, the model takes into account the activity of the cerebral cortex structures that modulate the autonomic control loops of blood circulation in the awake state and in various stages of sleep. The adequacy of the model is demonstrated by comparing its time series with experimental records of healthy subjects in the SIESTA database. The proposed model can become a useful tool for studying the characteristics of the cardiovascular system dynamics during sleep.